The knowledge and imagination in the Sufi novel of Abd al-Ilah Ibn Arafa, through his novel "Al-Hawamim". (Journal of Human Sciences, 2026)
This research paper deals with the duality of knowledge and imagination in the  Sufi novel of Abd al-Ilah Arafa through his novel "Al-Hawamim" .The writer combined the Sufi novel and the historical novel, as he returned to the tragedy of the fall of Andalusia, and the plight of the Andalusians...Abdul Ilah Arafa is trying to establish the Sufi novel and make it a cultural and narrative project that has its own religious, linguistic and historical specificity We will get acquainted with the significance of the title in the novel of al-Hawamim, separate between the historical, mystical and imaginative in this novel, and reveal the secrets of this new narrative achievement, and the failures of narration in it..